The Evaluation of the Effectiveness of the Optimized Technique of Transcleral Diodlaser Cyclophotocoagulation in Patients with Unstable Glaucoma - I. E. Shvailikova; E. I. Belikova (Oftalʹmologiâ, 2021)
Objectives: To evaluate the effectiveness of the optimized technique of transcleral diode laser cyclophotocoagulation (DCPC) in patients with unstable glaucoma.Methods. The retrospective analysis of outpatient records of patients diagnosed with open-angle compensated glaucoma, who underwent transcleral diodlaser DCPC in continuous-wave mode, has been performed. Totally, 44 outpatient records (44 eyes) have been analyzed.Results. The course of the postoperative period, patients’ complaints, and the ophthalmological status have been evaluated. The level of intraocular pressure (IOP) was determined on the day after the procedure, a week, 1, 3, 6 and 12 months after the operation. 12 months after the operation, the level of IOP decreased by 42.9 %. The number of antihypertensive drugs used by the end of the follow-up period decreased by 66.6 %: from 2.75 ± 0.4 to 1.0 ± 0.7 drugs (p = 0.001). The frequency of side effects was low and comprised 11.3 %. In 40 % of patients, manifestations of toxic-allergic reactions of the ocular surface to antihypertensive drugs decreased due to the possibility to reduce the frequency of instillations. The MCVA indicators remained stable throughout the entire follow-up period.Conclusion. Thus, the results of the conducted clinical study indicate that transcleral DCPC is an effective and safe technique with a high predicted result, since it compensates for the level of IOP, which allows to stabilize the progression of the glaucoma process. The method of trascleral DCPC provides a reduction and (or) correction of the hypotensive regime by reducing the number of antihypertensive drugs used. In patients with a toxic-allergic reaction from the ocular surface developed due to a prolonged use of antihypertensive drugs, it allows to reduce the symptoms and clinical manifestations by canceling and (or) reducing the number of antihypertensive drugs used, indirectly significantly improving the quality of life.